2012
DOI: 10.3758/s13423-011-0208-4
|View full text |Cite
|
Sign up to set email alerts
|

Second-order mappings in grapheme–color synesthesia

Abstract: Typically, the search for order in grapheme-color synesthesia has been conducted by looking at the frequency of certain letter-color associations. Here, we report stronger associations when second-order similarity mappings are examined-specifically, mappings between the synesthetic colors of letters and letter shape, frequency, and position in the alphabet. The analyses demonstrate that these relations are independent of one other. More strikingly, our analyses show that each of the letter-color mappings is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 28 publications
5
77
3
Order By: Relevance
“…Given this difficulty with establishing first-order relations, recent studies have begun to explore correspondence between the relationships among graphemes, on the one hand, and the relationships among colors, on the other (a second-order relation; Watson et al, 2012). Brang, Rouw, Ramachandran, and Coulson (2011) showed that similarity between synesthetic colors depended on similarity in the shapes of letters.…”
mentioning
confidence: 99%
“…Given this difficulty with establishing first-order relations, recent studies have begun to explore correspondence between the relationships among graphemes, on the one hand, and the relationships among colors, on the other (a second-order relation; Watson et al, 2012). Brang, Rouw, Ramachandran, and Coulson (2011) showed that similarity between synesthetic colors depended on similarity in the shapes of letters.…”
mentioning
confidence: 99%
“…In contrast, most previous studies showing the important role of visual shape in determining synesthetic color used only Latin alphabets, sometimes accompanied by characters of an additional language that shared visual features with Latin (e.g., Cyrillic) (Brang et al, 2011;Rich et al, 2005;Watson et al, 2012;Witthoft and Winawer, 2006). Indeed, the results of our datadriven clustering analysis showed that characters sharing not only sound similarity but also common visual features are clustered together in the color space, while characters of similar sound outnumber characters of similar visual shapes within the clusters (refer to Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Results so far, however, do not provide a consistent picture. Some researchers found that graphemes of a similar shape tended to induce similar synesthetic colors (Brang et al, 2011;Rich et al, 2005;Watson et al, 2012). Other researchers emphasized the importance of meaning over shape by showing that a similarly shaped character could take on different synesthetic color based on the semantic context in which it appeared (Dixon et al, 2006;Ramachandran and Hubbard, 2001).…”
Section: Introductionmentioning
confidence: 93%
“…The researchers mention a lot of reasons of grapheme-color synaesthesia: visual shape of grapheme (Brang et al, 2011;Watson et al, 2012); sound (Asano & Yokosawa, 2011; essence or meaning of the notions, with which the graphon is connected (Rich et al, 2005;Asano & Yokosawa, 2012); grapheme frequency (Beeli et al, 2007); color denomination, i.e. the order of letters in the color name (Cytowic, 1989;Motluk, 1997;Witthoft & Winawer, 2006;Watson et al, 2012); memory, for instance, toys, containing colorful letters, magnets on the refrigerator etc. (Witthoft & Winawer, 2006; a complex of enumerated factors (Asano & Yokosawa, 2011Watson et al, 2012).…”
Section: Factors Influencing the Sound-grapheme-color Associativitymentioning
confidence: 99%
“…the order of letters in the color name (Cytowic, 1989;Motluk, 1997;Witthoft & Winawer, 2006;Watson et al, 2012); memory, for instance, toys, containing colorful letters, magnets on the refrigerator etc. (Witthoft & Winawer, 2006; a complex of enumerated factors (Asano & Yokosawa, 2011Watson et al, 2012).…”
Section: Factors Influencing the Sound-grapheme-color Associativitymentioning
confidence: 99%